Desain Perangkat Pembelajaran Fisika Berbasis Konflik Kognitif untuk Kemampuan Pemecahan Masalah - Ricca Veronica; Gunawan Gunawan; Ahmad Harjono (Indonesian Journal of Teacher Education, 2022)
This study aims to design a feasible physics learning device integrating a cognitive conflict approach to accommodate students' problem-solving abilities. This Research and Development (R&D) study adopted the 4D model (Define, Design, Develop, and Disseminate), which was operationally simplified and restricted to the development stage due to the constraints of the Covid-19 pandemic and internet access limitations that prevented direct in-class implementation. The developed learning devices included a syllabus, lesson plans, student worksheets, and problem-solving test instruments. The feasibility of the product was evaluated through expert validation involving physics education lecturers and senior physics teachers, followed by a limited trial to assess user responses. The data were analyzed descriptively to determine the validity, reliability, and practicality percentage. The results indicated that the learning device achieved an average validity score of 88.38%, falling into the "highly valid" category, with an average reliability percentage agreement of 92.03%. Furthermore, the product received excellent responses from both physics education undergraduate students (99.23%) and high school students majoring in mathematics and natural sciences (99.56%). These findings confirm that the developed device meets the theoretical and practical feasibility requirements. It is concluded that the physics learning device based on the cognitive conflict approach is highly feasible to be implemented in actual physics instruction to help overcome misconceptions and stimulate students' problem-solving skills.